Improving Students’ Reading Comprehension Skill Through Making Inference at First Semester Students of STIE SAK Academic Year 2025/2026 - wijaya, Sukarta Kartawijaya; Al-Padli (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2026)
This research was a classroom action research, the purpose of this research was to find out the problems in the teaching and learning process and solve the problems. This research was conducted at first semester students of accounting major of STIE-SAK academic year 2025/2026. This classroom action research was conducted in two cycles, each cycle consisted three meetings. Based on the findings, it was found the improvements during the teaching and learning process. The result of the test in cycle one was 49.99% and increased to 88.88% in cycle two. The test was conducted based on the conversation text, the students were asked to make inferencing. The improvements were not only from the reading test but from the observation, fieldnotes. It also showed that the students’ attitude was also improved better. There were some factors improved the changes of students’ reading comprehension skill namely material, media, classroom activities and teaching way. Based on the result of the research, it could be concluded that through making inferencing had improved the students’ reading comprehension skill at first semester students of accounting major of STIE-SAK academic year 2025/2026.